MENINGKATKAN KOSA KATA BAHASA INGGRIS ANAK MELALUI MEDIA LOOSE PART - Khulusinniyah Khulusinniyah; Cindy Nor Halima (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2022)
English is one of the extra materials taught at RA Miftahus Surur Kalirejo Sumberwaru. In the classroom action research conducted on increasing children's English vocabulary, loose part media was chosen as a solution to solving problems found related to learning that is still monotonous. This study aims to describe the increase in English vocabulary using loose part media and to find out the results of increasing English vocabulary using loose part media. Through the four stages of CAR, namely planning, implementing, observing, and reflecting, the following conclusions can be drawn: Increasing English vocabulary in the learning process is carried out according to the RPPH which has been prepared and evaluated with predetermined assessment indicators. The results of the implementation of the implementation of loose part media to increase children's English vocabulary, experienced an increase in mastery percentage of 58.33%, in cycle I it increased to 83.33% in cycle II. This completeness percentage shows that the application of loose part media in learning activities can increase children's English vocabulary.